Geography of plant breeding systems, agroclimatic similarity, and agricultural productivity: Evidence from Nigeria - Takeshima, Hiroyuki (John Wiley & Sons, 2019)
Agroclimatic conditions and agricultural research and development (R&D) including plant breeding activities by the public sector are some of the most significant exogenous factors in the agricultural sector. However, the effects of the interactions between these two sets of factors on agricultural productivity have not been studied widely in developing countries, despite potentially important implications on their plant breeding strategies. Using three-wave panel data of agricultural households in Nigeria and spatial data on various agroclimatic parameters, we show that agricultural productivity and technical efficiency at the agricultural household level is significantly positively affected by the similarity of agroclimatic conditions between locations where agricultural households are located, and locations where major plant breeding institutes are located. These results hold after controlling for various socioeconomic characteristics of these households, including their physical distances to the breeding institutes. Findings are robust across parametric and nonparametric specifications such as Data Envelopment Method, and after addressing potential endogeneity of agroclimatic similarity and agricultural inputs variables in the production function. Productivity effects due to the locations of plant breeding institutes and resulting agroclimatic similarity can be potentially sizable given Nigeria's past productivity growth speed.